Crystal Structure and Morphology Analysis of Nd1+xBa2−xCu3O7 Oxide Alloy Surface Developed by Solid State Reaction Method - Eko Hadi Sujiono; Husain Ahmad; Fiskia Rera; Samnur Samnur (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2011)
This research has successfully prepared Nd1+xBa2−xCu3O7 oxide alloy which was developed using solid state reaction method with varying molar ratio x = 0.1 to x = 0,3. The process parameter observed was various synthesis routes that were different calcinations temperatures and sintering. In order to acquire the quality of the alloy, the homogeneity of the alloy were analyzed based on the result of EDAX (Energy dispersive X-ray). The composition of the material was analyzed in every variation of synthesis. Last, the crystal and morphology ofNd1+xBa2−xCu−3O−7 oxide alloy were analyzed based on the result of XRD (x-ray Diffraction) and SEM (Scanning Electron Microscope). The XRD measurements showed that crystal NdBaCuO has been formed. From the results of SEM images also showed that the greater the molar ratio x the particle size will be smaller.